(3eG de jbGd OGNd GdfaS GdHTQjIs - (3CHh RjO, YdG YeQs; (3GdfhHj, jSQGs; (3ShGM, SGde YHO GdeYRs ((3GdbGgQIs (3OGQ RMeI cJGH ddfTQs, 2025)
(3eG de jbGd OGNd GdfaS GdHTQjI, djS eLQO cJGH Hd gh QMdI UGObI eY GdPGJ, edjFI HGdPGJ GdgOa ef GdQMdI djS GdYHK HedaGJ GdeGVj, Hd GdJTLjY Ydi GcJTGa GdfaS hehGLgI GdCacGQ dJMSjf GdUMI GdfaSjI HCSdhH HSjW hefge, dfcf UGObjf eY CfaSfG HCf GdQMdI djSJ eLQO dMXGJ YGHQI CKfGA GdbQGAI, Hd gi QMdI WhjdI bO Jchf eQgbI aj HYV GdCMjGf hdcfgG JSJMb GdEUQGQ, JPcQ Cf cd jhe jMed aQUI LOjOI JfJXQc, QHeG Jchf CfJ GdQGhj jheG eGs
1 3 12 13
Keywords: (3GdJbOe GdTNUjs; (3GdUMI GdfaSjIs; (3GdfLGM GdTNUjs; (3JMbjb GdPGJs